PTH-134 Malnutrition Screening In Hospital Outpatients. (9th June 2014) - Gundkalli, Z; Blackwell, V; Howson, W; Williams, H
Abstract : Introduction: NICE Guidelines (2006) advocate the screening of all new hospital outpatients in order to identify individuals at risk of malnutrition within the community. However, existing data in support of outpatient screening are limited. To establish the utility of screening in specific outpatient settings, data were collected from targeted clinics. Patterns of risk associated with age, gender, ethnicity and 'new' or 'follow up' outpatient status were determined. Methods: The Malnutrition Universal Screening Tool (MUST) was used to assess the nutritional status of all individuals attending outpatient appointments at eight clinics at St. Mary's Hospital, Imperial College Healthcare NHS Trust. These were Gastroenterology, General Surgery, Geriatric Falls, Oncology, Chest and Allergy, Hypertension, Dermatology and Gynaecology/Urogynaecology. Appropriate action was taken as per guidelines for patients identified as 'at-risk'. Data were analysed using descriptive statistics, chi-square and logistic regression. Results: 585 outpatients were screened over a six week period (male 35.9%, n = 210/585; female 64.3%, n = 375/585; median age = 52, range 16–91 years; white ethnicity 57.7%, n = 338/585; non-white ethnicity 42.3%, n = 247/585). The overall prevalence of malnutrition risk was 12.1% (n = 71/585). There was a significantly higher risk of malnutrition in the young (16–24 years) and the elderly (≥ 75 years) (p = 0.04) and in individuals of white ethnicity (p = 0.0002). There was no difference in the prevalence of risk between new or follow up patients. There was a predictably high yield in Gastroenterology, General Surgery, Oncology and Geriatric Falls clinics. Low prevalence of risk was found in Hypertension and Gynaecology/Urogynaecology clinics. The Dermatology clinic yielded notable results with a 15.0% (n = 12/80) prevalence of risk. 8/12 of these patients were identified as medium risk (MUST score 1) due to a BMI of 18.5–20.0 kg/m 2 ; 7/8 were female and of white ethnicity. Conclusion: There have been no published studies of larger cohorts in a hospital outpatient setting. The prevalence of total malnutrition risk in this population, as determined by MUST, was lower at 12.1% compared to previously published smaller studies. 'At risk' groups were the young, the elderly and individuals of a white ethnic background. Many patients 'triggered' with a MUST score of 1, BMI 18.5–20.0 kg/m 2, which is in fact within the normal range. This was particularly notable in a cohort of young women attending the Dermatology clinic. The use of MUST in an outpatient setting requires further validation to ensure malnutrition risk is appropriately identified. Disclosure of Interest: None Declared.